Efficient aggregation technique for data privacy in wireless sensor networks. Issue 5 (1st September 2018) - Raja, Manjula; Datta, Raja
Abstract : In wireless sensor networks (WSNs), the existing cluster‐based private data aggregation techniques are energy‐intensive due to high message transmission complexity. Reliable data transmissions are also vital for resource constraint WSNs. To address these issues, the authors propose a reliability enabled private data aggregation technique that has message transmission complexity of O ( N ) . Every node in the cluster cleaves its data into n integrants using simple modular arithmetic with suitable prime moduli and transmits to the cluster heads (CHs) for intermediate aggregation. The CHs, in turn, forward the partial aggregate data to the base station where the final aggregate is recovered using an elegant Chinese remainder theorem. The authors use data privacy, communication overhead, and reliability metrics to gauge the performance of the proposed work. Numerical and simulation results demonstrate that the proposed solution outperforms the existing schemes having O ( N 2 ) communication complexity.